2012
DOI: 10.1007/s10620-012-2400-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-5p Inhibitor Enhances Chemosensitivity to Gemcitabine Via Upregulating Bim Expression in Pancreatic Cancer Cells

Abstract: These results prove that miR-17-5p negatively regulates Bim at the posttranscriptional level. We suggest that miR-17-5p inhibitor gene therapy would be a novel approach to chemosensitization for human pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…10). Previous studies identified Bim as direct targets of miR-17 [40, 45], miR-20a [27, 40], and miR-92a [40]. Xie et al .…”
Section: Discussionmentioning
confidence: 99%
“…10). Previous studies identified Bim as direct targets of miR-17 [40, 45], miR-20a [27, 40], and miR-92a [40]. Xie et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nagano and colleagues suggested that activation of the Wnt/beta-catenin signaling pathway mediates the miR-29a-induced resistance to gemcitabine in PDAC cells [95]. In another study, transfection of PANC-1 and BxPC-3 cells with an miR-17-5p inhibitor showed growth inhibition, spontaneous apoptosis, higher caspase-3 activation and increased chemosensitivity to gemcitabine [96]. Additionally, miR-205 was found to be consistently downregulated across pancreatic cancer specimens, making it a suitable therapeutic target.…”
Section: Mirnas Relate To Chemotherapy Treatment In Pdacmentioning
confidence: 99%
“…Conversely, miR-17-5p downregulates the proapoptotic member of the Bcl-2 protein family Bim, and PDAC cells transfected with miR-17-5p inhibitor showed growth inhibition, spontaneous apoptosis, higher caspase-3 activation, and increased chemosensitivity to gemcitabine [126]. Pathways delivering an antiapoptotic signal, such as PI3K/Akt, play also a pivotal role in the balance between proapoptotic and survival signals, which determines the fate of cancer cells.…”
Section: Microrna-based Mechanisms Of Anticancer Drug Resistance Imentioning
confidence: 99%